High-strength black sand pottery for furniture and preparation process of high-strength black sand pottery

By using benzamide compounds and zirconia with different hydroxyl groups as reinforcement agents in black sand pottery, the problem of low strength of black sand pottery is solved, and high-strength and high-toughness furniture ceramic materials are achieved to meet the needs of furniture use.

CN119161159APending Publication Date: 2024-12-20GUANTAO XIANGJIE CERAMIC CRAFT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411242899.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Traditional furniture materials have shortcomings in terms of strength and durability. Ordinary ceramics cannot fully meet the needs of furniture use, especially the low strength of black sand ceramics.

Method used

Use benzamide compounds containing different hydroxyl groups as binders, combined with alumina and zirconia as reinforcers, and control hydrogen bonding force and crystal growth by regulating the crystal phase mass ratio of zirconia, thereby enhancing the strength of black sand pottery and resilience.

Benefits of technology

The compressive strength and bending strength of black sand pottery have been significantly improved, and the hardness and toughness are balanced to meet the needs of furniture use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of unfired ceramics, and provides high-strength black sand pottery for furniture. Comprising the following raw materials in parts by weight: 3-5 parts of albite, 9-15 parts of cement, 6-10 parts of opal, 9-15 parts of lime, 3-5 parts of shoal mud, 15-25 parts of quartz sand, 9-15 parts of mica powder, 3-5 parts of wollastonite powder, 9-15 parts of talcum powder, 1-3 parts of an antibacterial agent, 1.2-2.4 parts of a dispersing agent, 0.5-1.5 parts of a defoaming agent, 2-4 parts of a coagulant aid, 0.3-0.8 part of a coloring agent, 3-6 parts of a reinforcing agent, 1-1.5 parts of a binder and 20-40 parts of water. And the binder is a benzamide compound. Through the technical scheme, the problem of low strength of the black sand pottery in related technologies is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of unfired ceramics, and in particular to high-strength black sand pottery for furniture and a preparation process thereof. Background Art

[0002] As people's living standards continue to improve, the requirements for furniture are becoming increasingly diverse. In the selection of furniture materials, people not only pay attention to beauty and practicality, but also put forward higher requirements for the strength and other properties of the materials. Although traditional furniture materials such as wood, plastic, and metal have their own advantages, they also have some shortcomings. Wood is easily affected by the environment and has problems such as deformation and cracking, and resources are limited; plastic may be lacking in strength and durability, and is not environmentally friendly; metal furniture is often bulky and has a relatively single style. Against this background, ceramic materials have gradually attracted people's attention with their unique advantages. Ceramics have the advantages of high hardness, corrosion resistance, high temperature resistance, and not easy to deform. However, ordinary ceramics may not be able to fully meet the use requirements of furniture in terms of strength. Therefore, the development of a high-strength black sand pottery for furniture is an urgent problem to be solved. Summary of the invention

[0003] The invention provides high-strength black sand pottery for furniture and a preparation process thereof, which solves the problem of low strength of black sand pottery in the related art.

[0004] The technical scheme of the present invention is as follows: The present invention provides a high-strength black sand pottery for furniture, comprising the following raw materials in parts by weight: 3-5 parts of albite, 9-15 parts of cement, 6-10 parts of opal, 9-15 parts of lime, 3-5 parts of sea mud, 15-25 parts of quartz sand, 9-15 parts of mica powder, 3-5 parts of wollastonite powder, 9-15 parts of talc, 1-3 parts of antibacterial agent, 1.2-2.4 parts of dispersant, 0.5-1.5 parts of defoaming agent, 2-4 parts of coagulant aid, 0.3-0.8 parts of colorant, 3-6 parts of reinforcing agent, 1-1.5 parts of binder, and 20-40 parts of water; The binder is a benzamide compound.

[0005] As a further technical solution, the benzamide compound includes one or more of 4-hydroxybenzamide, 3,4-dihydroxybenzamide, and 2,5-dihydroxy-N-(2-hydroxyethyl)benzamide.

[0006] In the present invention, by screening benzamide compounds containing different numbers of hydroxyl groups, the magnitude of the hydrogen bond force in the black sand pottery is controlled, so as to avoid the black sand pottery from generating large internal stress during the firing process due to excessive number of hydroxyl groups, causing deformation, cracking and other problems, thereby affecting the strength and performance of the black sand pottery.

[0007] As a further technical solution, the reinforcing agent consists of aluminum oxide and zirconium oxide.

[0008] As a further technical solution, the zirconium oxide consists of a first zirconium oxide and a second zirconium oxide, and the first zirconium oxide and the second zirconium oxide have different crystal phases.

[0009] As a further technical solution, the crystal phase of the first zirconium oxide is 3Y, and the crystal phase of the second zirconium oxide is 8Y.

[0010] As a further technical solution, the mass ratio of the first zirconium oxide to the second zirconium oxide is 2:1-3.

[0011] In the present invention, by regulating the mass ratio of the two crystal phases of zirconium oxide, not only the growth and arrangement order of the zirconium oxide crystals can be changed, affecting the voids and defects of the black sand pottery, but also the balance between the hardness and toughness of the black sand pottery can be achieved, thereby obtaining black sand pottery for furniture with the best strength.

[0012] As a further technical solution, the mass ratio of the first zirconium oxide to the second zirconium oxide is 1:1.

[0013] As a further technical solution, the antibacterial agent consists of copper oxalate, copper tungstate, apatite and zeolite.

[0014] As a further technical solution, the mass ratio of the copper oxalate, copper tungstate, apatite and zeolite is 2:1:2:5.

[0015] As a further technical solution, the defoaming agent includes one or more of polyoxyethylene polyoxypropylene pentaerythritol ether, polyoxyethylene polyoxypropanolamine ether, polyoxypropylene glycerol ether, and polyoxyethylene fatty alcohol ether.

[0016] As a further technical solution, at least one of the following technical features is also included: The dispersant includes one or more of sodium hexametaphosphate, sodium pyrophosphate, and sodium tripolyphosphate; The coagulant aid is composed of methyl cellulose, alginate, calcium chloride and propylene glycol alginate; The mass ratio of the methylcellulose, alginate, calcium chloride and propylene glycol alginate is 2:3:3:2; The colorant includes one or more of titanium dioxide, carbon black, chrome yellow, molybdenum cadmium red, and cobalt blue.

[0017] The present invention also provides a preparation process of high-strength black sand pottery for furniture, comprising the following steps: S1. Weigh albite, cement, opal, lime, sea mud and water, and fully hydrate them to obtain slurry; S2, add quartz sand, mica powder, wollastonite powder, talcum powder, antibacterial agent, dispersant, defoamer, coagulant, colorant, reinforcing agent, binder in sequence, stir evenly to obtain a rubber material; S3. The adhesive is hot pressed, cooled and solidified to obtain a brick, and high-strength black sand pottery is obtained after curing.

[0018] The working principle and beneficial effects of the present invention are: In the present invention, a benzamide compound is added as a binder to generate hydrogen bonds and van der Waals forces with other materials to improve the bonding effect between the raw materials, thereby enhancing the strength of the black sand pottery; aluminum oxide and zirconium oxide are added as reinforcing agents to further enhance the strength of the black sand pottery through their own high strength, high toughness, high temperature resistance, wear resistance and other properties. DETAILED DESCRIPTION

[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] Example 1 S1, weigh 3 parts of albite, 9 parts of cement, 6 parts of opal, 9 parts of lime, 3 parts of sea mud, and 20 parts of water, fully hydrate to obtain slurry; S2, add 15 parts of quartz sand, 9 parts of mica powder, 3 parts of wollastonite powder, 9 parts of talc, 0.2 parts of copper oxalate, 0.1 parts of copper tungstate, 0.2 parts of apatite, 0.5 parts of zeolite, 1.2 parts of sodium hexametaphosphate, 0.5 parts of polyoxyethylene polyoxypropylene pentaerythritol ether, 0.4 parts of methyl cellulose, 0.6 parts of alginate, 0.6 parts of calcium chloride, 0.4 parts of propylene glycol alginate, 0.3 parts of carbon black, 1.5 parts of first zirconium oxide, 1.5 parts of aluminum oxide, 1 part of 4-hydroxybenzamide, stir well to obtain a sizing material; S3. After hot pressing, cooling and solidification of the adhesive, the bricks are obtained. The bricks are moved into a curing kiln, heated to 70°C, cured for 7 hours, and cooled to 15°C to obtain high-strength black sand pottery.

[0021] Example 2 S1, weigh 4 parts of albite, 12 parts of cement, 8 parts of opal, 12 parts of lime, 4 parts of sea mud, and 30 parts of water, fully hydrate to obtain slurry; S2, sequentially add 20 parts of quartz sand, 12 parts of mica powder, 4 parts of wollastonite powder, 12 parts of talc, 0.4 parts of copper oxalate, 0.2 parts of copper tungstate, 0.4 parts of apatite, 1 part of zeolite, 1.8 parts of sodium pyrophosphate, 1 part of polyoxyethylene polyoxypropanolamine ether, 0.6 parts of methyl cellulose, 0.9 parts of alginate, 0.9 parts of calcium chloride, 0.6 parts of propylene glycol alginate, 0.5 parts of molybdenum cadmium red, 2 parts of first zirconium oxide, 2 parts of aluminum oxide, and 1.2 parts of 4-hydroxybenzamide, and stir well to obtain a sizing material; S3. After hot pressing, cooling and solidification of the adhesive, the bricks are obtained. The bricks are moved into a curing kiln, heated to 75°C, cured for 8.5 hours, and cooled to 20°C to obtain high-strength black sand pottery.

[0022] Example 3 S1, weigh 5 parts of albite, 15 parts of cement, 10 parts of opal, 15 parts of lime, 5 parts of sea mud, and 40 parts of water, fully hydrate to obtain slurry; S2, sequentially add 25 parts of quartz sand, 15 parts of mica powder, 5 parts of wollastonite powder, 15 parts of talc, 0.6 parts of copper oxalate, 0.3 parts of copper tungstate, 0.6 parts of apatite, 1.5 parts of zeolite, 2.4 parts of sodium tripolyphosphate, 1.5 parts of polyoxyethylene fatty alcohol ether, 0.8 parts of methyl cellulose, 1.2 parts of alginate, 1.2 parts of calcium chloride, 0.8 parts of propylene glycol alginate, 0.8 parts of cobalt blue, 3 parts of first zirconium oxide, 3 parts of aluminum oxide, and 1.5 parts of 4-hydroxybenzamide, and stir well to obtain a sizing material; S3. After hot pressing, cooling and solidification of the adhesive, the bricks are obtained. The bricks are moved into a curing kiln, heated to 80°C, cured for 10 hours, and cooled to 25°C to obtain high-strength black sand pottery.

[0023] Example 4 Compared with Example 1, the difference of Example 4 is that one part of 4-hydroxybenzamide is replaced by an equal amount of 3,4-dihydroxybenzamide.

[0024] Example 5 Compared with Example 1, the difference of Example 5 is that one part of 4-hydroxybenzamide is replaced by an equal amount of 2,5-dihydroxy-N-(2-hydroxyethyl)benzamide.

[0025] Example 6 Compared with Example 4, Example 6 is different in that 1.5 parts of the first zirconium oxide is replaced by an equal amount of the second zirconium oxide.

[0026] Example 7 Compared with Example 4, Example 7 is different in that 1.5 parts of the first zirconium oxide is replaced by 1.2 parts of the first zirconium oxide and 0.3 parts of the second zirconium oxide.

[0027] Example 8 Compared with Example 4, Example 8 is different in that 1.5 parts of the first zirconium oxide is replaced by 1 part of the first zirconium oxide and 0.5 parts of the second zirconium oxide.

[0028] Example 9 Compared with Example 4, Example 9 is different in that 1.5 parts of the first zirconium oxide is replaced by 0.75 parts of the first zirconium oxide and 0.75 parts of the second zirconium oxide.

[0029] Example 10 Compared with Example 4, Example 10 is different in that 1.5 parts of the first zirconium oxide is replaced by 0.6 parts of the first zirconium oxide and 0.9 parts of the second zirconium oxide.

[0030] Embodiment 11 Compared with Example 4, Example 11 is different in that 1.5 parts of the first zirconium oxide is replaced by 0.5 parts of the first zirconium oxide and 1 part of the second zirconium oxide.

[0031] Comparative Example 1 Compared with Example 1, Comparative Example 1 is different in that 4-hydroxybenzamide is not added.

[0032] The black sand pottery obtained in Examples 1 to 11 and Comparative Example 1 was tested according to the following method: 1. Compressive strength: Test the compressive strength of the sample according to the test method specified in GB / T 4704-1999 "Test method for compressive strength of ceramic materials".

[0033] 2. Bending strength: Test the bending strength of the sample according to the test method specified in GB / T 4741-1999 "Test method for flexural strength of ceramic materials".

[0034] The test results are shown in the following table: Table 1 Performance test results of black sand pottery obtained in Examples 1 to 11 and Comparative Example 1

[0035] Compared with Comparative Example 1, Example 1 adds 4-hydroxybenzamide, Example 4 adds 3,4-dihydroxybenzamide, and Example 5 adds 2,5-dihydroxy-N-(2-hydroxyethyl)benzamide. As a result, the compressive strength and flexural strength of Examples 1, 4, and 5 are better than those of Comparative Example 1, indicating that the addition of 4-hydroxybenzamide or 3,4-dihydroxybenzamide or 2,5-dihydroxy-N-(2-hydroxyethyl)benzamide can improve the strength of black sand pottery. Among Examples 1, 4, and 5, the compressive strength and flexural strength of Example 4 are better than those of Examples 1 and 5, indicating that when 3,4-dihydroxybenzamide is added, the strength of the obtained black sand pottery is better.

[0036] Compared with Examples 4 and 6, Examples 7 to 11 simultaneously added the first zirconium oxide and the second zirconium oxide, and the compressive strength and flexural strength of Examples 7 to 11 were better than those of Examples 4 and 6, indicating that the first zirconium oxide and the second zirconium oxide played a synergistic role and could further improve the strength of the black sand pottery. In Examples 7 to 11, different mass ratios of the first zirconium oxide and the second zirconium oxide were added, and the compressive strength and flexural strength of Examples 8 to 10 were better than those of Examples 7 and 11, indicating that when the mass ratio of the first zirconium oxide to the second zirconium oxide was 2:1 to 3, and the preferred ratio was 1:1, the strength of the obtained black sand pottery was optimal.

[0037] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-strength black sand pottery for furniture, It is characterized in that The invention comprises the following raw materials in parts by weight: 3-5 parts of albite, 9-15 parts of cement, 6-10 parts of opal, 9-15 parts of lime, 3-5 parts of sea mud, 15-25 parts of quartz sand, 9-15 parts of mica powder, 3-5 parts of wollastonite powder, 9-15 parts of talc, 1-3 parts of antibacterial agent, 1.2-2.4 parts of dispersant, 0.5-1.5 parts of defoaming agent, 2-4 parts of coagulant aid, 0.3-0.8 parts of colorant, 3-6 parts of reinforcing agent, 1-1.5 parts of binder and 20-40 parts of water; the binder is a benzamide compound.

2. The high-strength black sand pottery for furniture according to claim 1, It is characterized in that The benzamide compound includes one or more of 4-hydroxybenzamide, 3,4-dihydroxybenzamide, and 2,5-dihydroxy-N-(2-hydroxyethyl)benzamide.

3. The high-strength black sand pottery for furniture according to claim 1, It is characterized in that The reinforcing agent consists of aluminum oxide and zirconium oxide.

4. The high-strength black sand pottery for furniture according to claim 3, It is characterized in that The zirconium oxide consists of a first zirconium oxide and a second zirconium oxide, and the first zirconium oxide and the second zirconium oxide have different crystal phases.

5. The high-strength black sand pottery for furniture according to claim 4, It is characterized in that The crystal phase of the first zirconium oxide is 3Y, and the crystal phase of the second zirconium oxide is 8Y.

6. The high-strength black sand pottery for furniture according to claim 4, It is characterized in that The mass ratio of the first zirconium oxide to the second zirconium oxide is 2:1-3.

7. The high-strength black sand pottery for furniture according to claim 1, It is characterized in that The antibacterial agent consists of copper oxalate, copper tungstate, apatite and zeolite.

8. The high-strength black sand pottery for furniture according to claim 1, It is characterized in that The defoaming agent includes one or more of polyoxyethylene polyoxypropylene pentaerythritol ether, polyoxyethylene polyoxypropanolamine ether, polyoxypropylene glycerol ether, and polyoxyethylene fatty alcohol ether.

9. The high-strength black sand pottery for furniture according to claim 1, It is characterized in that Also includes at least one of the following technical features: The dispersant includes one or more of sodium hexametaphosphate, sodium pyrophosphate, and sodium tripolyphosphate; The coagulant aid is composed of methyl cellulose, alginate, calcium chloride and propylene glycol alginate; The colorant includes one or more of titanium dioxide, carbon black, chrome yellow, molybdenum cadmium red, and cobalt blue.

10. A preparation process of high-strength black sand pottery for furniture according to any one of claims 1 to 9, It is characterized in that The following steps are involved: S1. Weigh albite, cement, opal, lime, sea mud and water, and fully hydrate them to obtain slurry; S2, add quartz sand, mica powder, wollastonite powder, talcum powder, antibacterial agent, dispersant, defoamer, coagulant, colorant, reinforcing agent, binder in sequence, stir evenly to obtain a rubber material; S3. The adhesive is hot pressed, cooled and solidified to obtain a brick, and high-strength black sand pottery is obtained after curing.